The hitch-hiker - Lupino, Ida, 1918-1995; O'Brien, Edmond, 1915-1985; Lovejoy, Frank, 1914-1962; Talman, William, 1915-1968; Cinetel Films ([Hollywood, CA] : Filmakers, 1953)
A classic, tension-packed, three-way dance of death about two middle-class American homebodies on vacation in Mexico on a long-awaited fishing trip. Suddenly their car and their very lives are commandeered by psychopathic serial killer Emmett Myers.
Originally distributed by RKO Radio Pictures, Inc.
Edmond O'Brien, Frank Lovejoy, William Talman.
Director of Photography, Nicholas Musuraca; editor, Douglas Stewart; music by Leith Stevens.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: Serial murderers -- Drama; Hitchhiking -- Drama; Vacations -- Mexico -- Drama; Thrillers (Motion pictures); Film noir; Feature films; Internet videos; Streaming video